On the Synthesis and Reactivity of 2,3-Dihydropyrrolo[1,2-a]quinazolin-5(1H)-ones - Sutherell, Charlotte; Ley, Steven (Thieme, 2017)
An improved, scalable synthetic route to the quinazolinone natural product 2,3-dihydropyrrolo[1,2-a]quinazolin-5(1H)-one is reported. The applicability of this method to analogue synthesis and the synthesis of related natural products is explored. Finally, reactivity of the scaffold to a variety of electrophilic reagents, generating products stereoselectively, is reported.
Keywords: 3405 Organic Chemistry; 34 Chemical Sciences; Natural Products; Complementary and Integrative Health; Generic health relevance